Illegitimate Citizenship Rules - Leticia Saucedo; Rose Cuison Villazor (Washington University Law Review, 2020)
In 2017, the Supreme Court decided Sessions v. Morales-Santana, a challenge to 8 U.S.C. § 1409, the law governing the conferral of U.S. citizenship to children born abroad to parents who are U.S. citizens. As the Court noted in a forceful opinion, § 1409 imposed different and more onerous physical presence requirements on unwed fathers than unwed mothers, making it difficult for nonmarital fathers to transmit their U.S. citizenship to their foreign-born children. Such distinctions, the Court concluded, were rooted in archaic gender stereotypes and thus incompatible with equal protection principles. Although Morales-Santana corrected the gender discrimination inherent in § 1409, it said nothing of the statute’s other constitutionally infirm provisions. Although it has drawn little attention, § 1409 also discriminates on the basis of illegitimacy, which like gender, is a quasi-suspect classification for purposes of equal protection law. Specifically, § 1409 requires nonmarital children to prove that they have been legitimated by their unwed U.S. citizen fathers to establish their derivative citizenship claim. By contrast, foreign-born children in wedlock need not show that they have been legitimated; by virtue of their parents’ marriage, they are legally recognized as “legitimate” children. These legitimation requirements have made it more difficult for foreign-born nonmarital children of U.S. citizen parents to prove what should be regarded as their pre-existing citizenship. Crucially, in general, laws such as these that distinguish on the basis of a parents’ marital status constitute illegitimacy discrimination. Yet, the Court in Morales-Santana neglected to acknowledge this unequal treatment of nonmarital children, focusing instead on how § 1409 discriminated on the basis of gender and effectively allowing this unconstitutional practice to continue. This Article calls attention to the prevalence of illegitimacy classifications in immigration law by identifying what we term “illegitimate citizenship rules.” In highlighting the pervasiveness of this form of discrimination, this Article makes three contributions. As a descriptive matter, these rules demonstrate the unfinished project within equal protection law of eviscerating discrimination against nonmarital children, which includes the treatment of such children in immigration law. As a doctrinal matter, the Article argues that the Supreme Court’s narrow focus on the sex equality dimension of § 1409 rendered invisible the discrimination against nonmarital children. Finally, as the Article makes clear, by discriminating against nonmarital children, illegitimate citizenship rules promote and perpetuate the “traditional” family and thus discriminate against those families that do not comport with the heterosexual marital family model. The Article concludes by recommending that Congress seize the opportunity created by Morales-Santana to address and eventually eradicate the ongoing discrimination against nonmarital children who are born abroad.
Keywords: 8 USC 1409; Family law; Citizenship; Equal protection; Immigration law; Discrimination; Sessions v. Morales-Santana 137 S. Ct. 1678; Marital status